The Impact of Screen-Use on Cognitive Function: A Pilot Study - Jóhanna Ásta Þórarinsdóttir 1992- (2015)
Screen-use and its impact on cognitive function has not been studied thoroughly. The main intention of the present study was to see if screen-use has an impact on cognitive function. Furthermore, the aim was to look at possible moderating effects of factors such as depression, sleep and psychosomatic symptoms that have been shown to decrease cognitive function in earlier studies. A total of 45 undergraduate students at the Reykjavik University, Iceland were recruited. The participants answered a questionnaire that included items about depression, sleep, psychosomatic symptoms and screen-use. The subjects were then asked to complete a computerized Sustained Attention to Response Task (SART) and a Stroop Color-Word task. The results revealed a significant main effect of type of stroop task and a significant three-way interaction between type of stroop task, screen-use, and depression. Furthermore, a significant two-way interaction between SART time (beginning, middle, end) and screen-use was revealed. No other main effects or interactions were significant. Results indicate an effect of screen use on cognitive function. The moderators in general did not impact the relationship between screen use and cognitive function except for depression and stroop task. Keywords: cognitive function, screen-use, stroop, depression, psychosomatic symptoms, sleep-length, sleep-quality Áhrif skjááhorfs á hugræna virkni hafa ekki verið skoðuð mikið af fyrri rannsóknum. Aðal áhersla rannsóknarinnar var að skoða hvort skjááhorf hafi áhrif á hugræna virkni. Einnig var markmiðið að skoða hugsanleg samvirkniáhrif þátta eins og þunglyndi, svefn og sállíkamleg einkenni sem sýnt hafa fram á tengsl við hugræna virkni í fyrri rannsóknum. Fjörutíu og fimm nemar í Háskólanum í Reykjavík tóku þátt. Þátttakendur svöruðu spurningalista sem innihélt spurningar um þunglyndi, svefnmynstur, sállíkamleg einkenni og skjááhorf. Þátttakendur gengust svo undir athyglispróf Sustained Attention to Response Task (SART) og stroop próf Stroop Color-Word task. ...